PENERAPAN METODE RGEC DALAM MENILAI TINGKAT KESEHATAN DAN KINERJA PT. BANKALTIMTARA PERIODE TAHUN 2015 – 2019 - Sabri Nurdin (Jurnal Eksis, 2020)
The good performance of bank is required to maintain public confidence so the health bank level is maintained. This research’s purpose is to knowing and analyzing the health level and the performance of PT. Bankaltimtara. using the approach of RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) period of 2015-2019. The method used in this research is descriptive method with quantitative approach. The result of this research are assessment of performance and health levels on Risk Profile’s factors as measured by the ratio of NPL and  can be categorized as good, but in ratio of LDR was not good because it has a very high LDR. Assessment of performance and health levels on Good Corporate Governance (GCG)’s factors overall can be categorized as good. Assessment of performance and health levels on Earning’s factors that was measured using ROA ratio can be be categorized as good categorized as good. The ratio of NIM can be categorized as excellent. The Ratio of BOPO can be categorized as good Assessment of performance and health levels on Capital’s factor that are measured using the CAR can be categorized as excellent Keywords: Performance Bank, Bank Health Level, Risk Profile, Good Corporate                   Governance, Earning, and Capital (RGEC) Method